Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0039820
|View full text |Cite|
|
Sign up to set email alerts
|

The CUPID (Cultural and Psychosocial Influences on Disability) Study: Methods of Data Collection and Characteristics of Study Sample

Abstract: Background The CUPID (Cultural and Psychosocial Influences on Disability) study was established to explore the hypothesis that common musculoskeletal disorders (MSDs) and associated disability are importantly influenced by culturally determined health beliefs and expectations. This paper describes the methods of data collection and various characteristics of the study sample. Methods/Principal Findings A standardised questionnaire covering musculoskeletal symptoms, disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 27 publications
1
89
0
16
Order By: Relevance
“…After elimination of subjects who did not meet the inclusion criteria that had been specified in the protocol (age 20–59 years, worked in current job for at least 12 months), and a further 317 for whom critical information was missing (eg, on sex or age), the CUPID study sample comprised a total of 12 426 participants. Further details of exclusions and the characteristics of the study sample have been reported elsewhere 23. For the purposes of this report, we excluded an additional 10 participants with missing information on sickness absence for musculoskeletal pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After elimination of subjects who did not meet the inclusion criteria that had been specified in the protocol (age 20–59 years, worked in current job for at least 12 months), and a further 317 for whom critical information was missing (eg, on sex or age), the CUPID study sample comprised a total of 12 426 participants. Further details of exclusions and the characteristics of the study sample have been reported elsewhere 23. For the purposes of this report, we excluded an additional 10 participants with missing information on sickness absence for musculoskeletal pain.…”
Section: Resultsmentioning
confidence: 99%
“…We present here, an analysis of data on sickness absence from the CUPID (Cultural and Psychosocial Influences on Disability) study, which used standardised methods to collect information on 47 occupational groups in 18 countries 23. The study focused on disability from musculoskeletal complaints, which in many countries are the major reason given for longer-term sickness absence 24–26.…”
Section: Introductionmentioning
confidence: 99%
“…"How satisfied have you been with your job as a whole, taking everything into consideration?" [93]; "Does your job consist of constantly repeated tasks, meaning that you do the same thing hour after hour?" [94].…”
Section: Methods Of Assessment and Classificationmentioning
confidence: 99%
“…26 Detailed information about the data collection and sample characteristics can be found elsewhere. 20 Ethical review and approval were obtained prior to data collection, from institutional review committees in each country, and from the University of Texas Health Science Center Committee for the Protection of Human Subjects.…”
Section: Study Design and Participantsmentioning
confidence: 99%